Effects of benzyl viologen on increasing NADH availability, acetate assimilation, and butyric acid production by Clostridium tyrobutyricum. Issue 2 (4th November 2020) - Fu, Hongxin; Lin, Meng; Tang, I‐Ching; Wang, Jufang; Yang, Shang‐Tian
Abstract: Clostridium tyrobutyricum produces butyric and acetic acids from glucose. The butyric acid yield and selectivity in the fermentation depend on NADH available for acetate reassimilation to butyric acid. In this study, benzyl viologen (BV), an artificial electron carrier that inhibits hydrogen production, was used to increase NADH availability and butyric acid production while eliminating acetic acid accumulation by facilitating its reassimilation. To better understand the mechanism of and find the optimum condition for BV effect on enhancing acetate assimilation and butyric acid production, BV at various concentrations and addition times during the fermentation were studied. Compared with the control without BV, the addition of 1 μM BV increased butyric acid production from glucose by ∼50% in yield and ∼29% in productivity while acetate production was completely inhibited. Furthermore, BV also increased the coutilization of glucose and exogenous acetate for butyric acid production. At a concentration ratio of acetate (g/L) to BV (mM) of 4, both acetate assimilation and butyrate biosynthesis increased with increasing the concentrations of BV (0–6.25 μM) and exogenous acetate (0–25 g/L). In a fed‐batch fermentation with glucose and ∼15 g/L acetate and 3.75 μM BV, butyrate production reached 55.9 g/L with productivity 0.93 g/L/h, yield 0.48 g/g, and 97.4% purity, which would facilitate product purification and reduce production cost. Manipulating metabolic flux and redox balance via BV and acetate addition provided a simple to implement metabolic process engineering approach for butyric acid production from sugars and biomass hydrolysates. Abstract : Clostridium tyrobutyricumproduces butyric acid as the main product in the presence of benzyl viologen (BV), which diverts the electron used for hydrogen production to produce more NADH that pulls the carbon flux from acetyl‐CoA to butyryl‐CoA and leads to acetate reassimilation. A high butyric acid yield (>0.4 g/g) and purity (>95%) thus can be produced from glucose and acetate with BV addition in the medium.